Extensión y unificación de la jurisprudencia / Artículo final de sustentación: unificación y extensión de la jurisprudencia (2015)
This research is grounded in the study of Colombian jurisprudence and doctrine regarding the issue of the extension and unification starting from the year 1984 to the 1437 Act of 2011. Exactly the problem with this is the importance that currently has the Jurisprudence even on the same Law, placing the term in a relevant precedent, starting from here the article on the origin and cause of this development was shaped. A detailed study on the subject was conducted by consulting multiple sources of information and understanding how you are significant figures form part of the study of law and in the administrative field.